Case report: A report of the complete pathological response of intrahepatic cholangiocarcinoma after conversion therapy - Zhang, Xi; Tang, Hao; Fan, Jun; Wang, Rui; Han, Yunwei; Su, Song; Gan, Yu; Peng, Fangyi; Rao, Mingyue; Zhang, Jianwen; Li, Bo; Yang, Xiaoli (Frontiers in Immunology, 2022)
Cholangiocarcinoma (CCA) is a rare disease with poor prognosis, and surgery remains the only curative treatment option. However, surgery is inappropriate for the majority of patients with CCA. Conversion therapy may provide opportunities for the surgical treatment of these patients. Herein, we describe a patient with intrahepatic CCA who was first treated with albumin-bound paclitaxel, cisplatin, and gemcitabine in combination with camrelizumab. The patient then successfully underwent surgery and achieved pathological complete remission. This report can serve as a reference for clinicians regarding conversion therapy for intrahepatic CCA.